Studying The Mental Health Status Of Nurses In The Era Of Covid-19 (A Rapid Review Study In Iran) - Mahshid Zare; Zahra Kavosi; Sedighe Sadat Tabatabaei Far (بیمارستان)
Background and purpose: The COVID-19 pandemic has brought a significant shock to healthcare systems worldwide, including Iran. The mental health of nurses, who have been at the forefront of the fight against the virus, has been profoundly impacted. This study aims to examine the mental health status of Iranian nurses during the pandemic. Methods: This rapid review was conducted by searching keywords such as "Mental Health," "Nurse," and "COVID-19" in databases including Google Scholar, PubMed, ScienceDirect, ProQuest, Mag Iran, and Civilica. Articles were selected based on their titles, abstracts, and full texts in alignment with the study’s research objectives. Results: The reviewed studies revealed a range of mental health disorders among nurses working in COVID-19 wards, with stress, anxiety, and depression being the most common. Several factors, such as demographic variables and the specific departments where nurses served, were identified as influencing their mental health. Given that the mental health of nurses affects the quality of care, resilience, and job satisfaction, various strategies have been proposed to improve their mental health. Conclusion: The findings suggest that the mental health status of nurses is not at an optimal level, and neglecting this issue could lead to long-term harm to the healthcare system and its economic stability. It is recommended that healthcare managers and policymakers implement appropriate measures to address this critical concern.